2008
DOI: 10.1007/s12072-008-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled pilot study of Pentoxifylline in patients with non-alcoholic steatohepatitis (NASH)

Abstract: Purpose Tumor necrosis factor-a (TNF-a) is implicated in non-alcoholic steatohepatitis (NASH). Pentoxifylline inhibits TNF-a. We wanted to evaluate the efficacy of Pentoxifylline on NASH patients. Methods Patients with biopsy proven NASH and persistently elevated alanine aminotransferase (ALT) greater than 1.5 times the upper limit of normal were randomized to 3 months of treatment with a step 1 American Heart Association diet and daily exercise with Pentoxifylline or placebo. Liver function tests, serum lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 20 publications
5
57
1
7
Order By: Relevance
“…The present findings suggest that modulation of the inflammatory response is a key factor in the progression of NASH, in accordance with previous report supporting the potential clinical utility of a drug with anti-inflammatory effects in patients having predisposing factors of NAFLD and NASH. 19 In the present study, the histopathological changes of the hepatic tissue in the HFHC fed group demonstrated hepatic cell injury, which led to the release of excessive amounts of intracellular hepatic transaminases into the serum. The structural distortion and the functional impairment of the hepatic cells by NASH were associated with increase in insulin level and high insulin resistance.…”
Section: Discussionsupporting
confidence: 46%
“…The present findings suggest that modulation of the inflammatory response is a key factor in the progression of NASH, in accordance with previous report supporting the potential clinical utility of a drug with anti-inflammatory effects in patients having predisposing factors of NAFLD and NASH. 19 In the present study, the histopathological changes of the hepatic tissue in the HFHC fed group demonstrated hepatic cell injury, which led to the release of excessive amounts of intracellular hepatic transaminases into the serum. The structural distortion and the functional impairment of the hepatic cells by NASH were associated with increase in insulin level and high insulin resistance.…”
Section: Discussionsupporting
confidence: 46%
“…6). One RCT found no impact on plasma LDL-C, HDL-C and TG [80]. There was no significant publication bias for assessed outcomes (not reported).…”
Section: Anti-tnf-α Agents (Pentoxifylline)mentioning
confidence: 98%
“…The anti-TNF-α agent pentoxifylline has been evaluated in four RCTs in NASH [78][79][80][81] (three with low risk of bias, two assessing post-treatment histology) (ESM Table 4). …”
Section: Anti-tnf-α Agents (Pentoxifylline)mentioning
confidence: 99%
“…4 RCTs have shown that PTX 1200 mg daily appears to improve histology via reduction in steatosis, inflammation, and even fibrosis. [79][80][81][82][83] Further studies are needed to confirm these findings.…”
Section: 77mentioning
confidence: 99%